فاعلية تمرينات عقلية في الاداء المهاري للاعبين الشباب بالكرة الطائرة - علي, أنيس حسين; ابراهيم, ميثم لطيف (Sulaimani Journal for Humanities, 2018)
The research aims to identify the nature of mental processes Especially (relaxation, mental perception, concentration of attention) and knowledge of their effectiveness in the skills of beating and receiving. The researchers used the experimental approach in the style of the two groups by adopting the tribal and remote tests of the two research fieldsIn addition to selecting the appropriate statistical means to process data and know the extent of improvement in the level of skill performanceThe results of the research were encouraging, as the exercise improved the skill level of the experimental research sample compared to the control sample and also the level of mental processes adopted for the same sample in the current research. The researchers recommended the need to adopt the mental exercises prepared in this research during the learning process because of their role in the good handling of the position skilled and skilled skill required from the working groups to achieve the skills with the best possible performance. Work on other sports activities.